Kesesuaian Model Hidrograf Satuan Sintetis ITB pada Sub Daerah Aliran Sungai (DAS) Landak - Nirmala, Azwa; Hafiyyan, Qalbi (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
In this study, flood hydrograph analysis was conducted in the Landak river sub-watershed. The analysis used the synthetic unit hydrograph method, namely HSS ITB-1 and 2 (exact and numerical). The advantage of this method is that this method is developed based on the physical properties and characteristics of river basins in Indonesia. The purpose of this study was to see the suitability of the ITB synthetic unit hydrograph model in the Landak River sub-watershed. The suitability was measured by comparing it with the existing measured discharge data. The results of the HSS ITB modeling provide good agreement with the measured discharge. The HSS ITB-2 Exact model is suitable for use in the Ambawang and Ngabang sub-watersheds. This can be seen from the differences between the HSS ITB-2 Exact flood discharges, which have the smallest difference with the measured flood discharge compared to other HSS ITB models, namely 23.75% for the Ambawang sub-watershed, 55.78% for the Ngabang sub-watershed and 143.14% for the Landak sub-watershed. For the Serimbu sub-watershed, the HSS ITB-1 Numerical model is the model with the lowest error rate compared to other HSS ITB models, which is 25.24%. The results of this study are expected to be a reference in conducting flood discharge analysis for use in planning water structures at the research location.